Privacy protection mechanism of on-demand disclosure on blockchain - Shaozhuo LI; Na WANG; Xuehui DU (网络与信息安全学报, 2020)
Privacy protection has become the key problem that blockchain technology must solve from theory to practice.There is a privacy protection requirement of on-demand disclosure in practical applications.Inspired by multicast secure communication mechanism,a privacy protection mechanism of on-demand disclosure on blockchain was proposed.This mechanism improves the RSA based anonymous multi receiver encryption scheme to realize the disclosure of the private data on the blockchain only to the permitted informed,the anonymity protection of the informed and the traceability of the privacy disclosure.The Quorum blockchain privacy protection mechanism is adopted to realize the safe and efficient distribution of the key between the owner of the private information and the informed.Finally,it is proved that PPM-ODB mechanism can guarantee the privacy of privacy data and its superiority in time and storage cost,and it is suggested that the number of informed people should be less than 100 to obtain a good user experience.